Geomechnical Characterization of Lateritic Soil by Combining Crushed Granite and Low Content of Cement - Mbengue, Marie Thérèse Marame; N’tsoukpoe, Jeannot Komi; Messan, Adamah; Ayite, Mawuénya Xolali Dany (Civil Engineering Journal, 2025)
Lateritic soils, which are widespread in intertropical regions and traditionally used as pavement sub-base layers in Burkina Faso, often exhibit low geomechanical performance, thereby limiting their long-term durability under increasingly heavy traffic loads. This study investigates a combined stabilization approach consisting of incorporating 20% of 10/20 crushed granite aggregates together with low cement content (0%, 1%, 2%, and 3%). The objective was to improve both the mechanical properties and fracture behavior of these soils, while reducing the environmental footprint associated with cement use. Accordingly, an experimental program was carried out, including geotechnical tests (maximum dry density, optimum moisture content, and CBR at 95% compaction) and mechanical characterizations (unconfined compressive strength, indirect tensile strength, Young’s modulus, and full stress–strain behavior under uniaxial compression). The results revealed substantial improvements when 20% aggregates and 3% cement were added to the raw soil: the maximum dry density increased by approximately 5%, the CBR by 2253%, the compressive strength by 134%, the indirect tensile strength by 85%, and the Young’s modulus by 195%. Regarding fracture behavior, the same mixture showed an enhanced energy absorption capacity, with increases of approximately 40% for fracture energy, 65% for peak energy, 87% for elastic energy, 18% for plastic energy, and 5% for post-peak energy. These findings confirm that the combination of crushed aggregates and low cement content produces a synergistic effect, yielding a material that is stronger, stiffer, more water resistant, and more ductile. Thus, innovative stabilization approach represents a promising alternative for sustainable road construction.